2018
DOI: 10.2209/tdcpublication.2017-0007
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Synthase (NOS) Isoform Expression after Peripheral Nerve Transection in Mice

Abstract: Localization of the nitric oxide (NO)-producing enzyme, nitric oxide synthase (NOS), and its functions are currently being investigated in several tissues and organs. It has been suggested that NO is involved in nerve cell death and the development of neurodegenerative disease. The purpose of this study was to immunohistochemically investigate expression of NOS to clarify its function in the degeneration and regeneration of transected mouse sciatic nerve. Scattered neuronal NOS (nNOS)-positive Schwann cells ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Recent studies have found that NO produced by upregulated iNOS after mDC activation controls the balance of effector DCs and regulatory DCs, which is accomplished by inhibiting NF-κB signaling and inflammatory body activity [42,43,44]. We found that although the number of CD11c + CD11b + effector DCs producing IL-12, TNF-α, and IL-6 in iNOS ‒/‒ mice to be increased, the percentage of CD11c + CD11b + regulatory DCs expressing IL-10 and PD-1 was the same as that of wild type mice.…”
Section: Regulation Of Dendritic Cells Differentiation By Inosmentioning
confidence: 99%
“…Recent studies have found that NO produced by upregulated iNOS after mDC activation controls the balance of effector DCs and regulatory DCs, which is accomplished by inhibiting NF-κB signaling and inflammatory body activity [42,43,44]. We found that although the number of CD11c + CD11b + effector DCs producing IL-12, TNF-α, and IL-6 in iNOS ‒/‒ mice to be increased, the percentage of CD11c + CD11b + regulatory DCs expressing IL-10 and PD-1 was the same as that of wild type mice.…”
Section: Regulation Of Dendritic Cells Differentiation By Inosmentioning
confidence: 99%
“…These inhibitory effects of three drugs mean that HOs activation regulates oxidative stress during Wallerian degeneration. Interestingly, NOS2 protein expression was not found in the Western blot analysis (data not shown) because NOS2 is not present in sciatic nerves (Kikuchi et al., 2018). These three drugs also inhibited HO2 on 3DIV because CrMP, SnMP, and SnPP by competing with heme for binding HOs suppress both HO1 and HO2 (Figure 5(c)).…”
Section: Resultsmentioning
confidence: 96%